Addressing the Teacher Preparation Gap for ELs: A Memo for Teacher Administrators, Teacher Educators & Policy Advocates (Iris Journal of Scholarship)
English Learners as a student population are increasing in US Schools and migrating to new areas. A review of research shows that teachers are underprepared to meet the unique linguistic and cultural needs and leverage the strengths of this student population. This memo explores the problem space, reviews relevant research and current practices in pre-service education and in-service professional development. Guiding the research and current practices are two essential questions: Is this preparation method effective in changing teacher practice and improving student outcomes? Is this method permeating the educational sphere enough to produce change? The memo details a three prong solution to addressing the teacher preparation gap and concludes by discussing limitations of the memo and approach.
Keywords: English Learners; Language Minority Learner; Teacher Education; Teacher Professional Development; Pre-Service; In-Service; Coaching; Teacher preparation; Pre-Service Practicum